Assessment of smear layer removing efficacy of different irrigation activation devices in mandibular premolar teeth using a scanning electron microscope: An in vitro comparative study - Saurabh Sudesh Chodankar; P Ashwini; N Meena; Vishwas Gowda; Nikitha D'souza (Wolters Kluwer Medknow Publications, 2023)
Aim: The purpose of this study was to assess and compare the effectiveness of three different irrigation activation systems in removing smear layer in single-rooted mandibular premolars using scanning electron microscope (SEM). Materials and Methods: Fifty-six extracted single-rooted mandibular premolars were included in the study (n = 56). The teeth were decoronated, working length was determined, and canals were prepared till #30/0.09, with 5.25% sodium hypochlorite and saline as working solution. Final irrigation was performed with 5 mL of 17% ethylenediaminetetraacetic acid solution using three different activation systems. Teeth were randomly divided into four groups: Group A (control group) - conventional syringe irrigation with 30-G single side-vented needle; Group B (passive ultrasonic irrigation [PUI] method) - PUI with #20 Irrisafe ultrasonic files activated for 1 min; Group C (sonic activation) - EndoActivator system using the yellow tip (#20/0.04) activated for 1 min; and Group D - Tornado Disinfection Kit using GF Brush for 20-30 s as per the manufacturer's instructions. The samples were sectioned and subjected to SEM at × 2500 magnification. The efficacy of smear layer removal was assessed and scored by two operators. The collected data were analyzed statistically using Chi-square test (P < 0.05). Results: There was no statistically significant difference observed between the three different activation groups and the control group (P < 0.05). Conclusion: PUI performed better than all the study groups in removing smear layer from coronal, middle, and apical third of root canals. EndoActivator and Tornado Disinfection Kit performed similar in coronal and middle third, but the efficacy in apical third was inferior to the PUI group.